Abundance of frugivorous birds and richness of fruit resource: is there a temporal relationship? (2000)
It is believed that the abundance of frugivorous birds in a landscape is related to the fruit supply in each vegetation type. Although some evidence for this relationship exists at the bird community level, it has seldom been demonstrated in frugivorous bird species that inhabit different vegetation types or succesional gradients in a landscape. In this study, I assessed the temporal relationships between the abundance of individual frugivorous bird species and the richness of fruiting ornithochorous plant species in different, contiguous vegetation types in a neotropical landscape. Monthly variation in abundance of each frugivorous bird species cannot be explained by the richness of fruiting ornithochorous plant species in each vegetation type. I found only two positive correlations out of a possible 42 (fourteen bird species in three vegetation tvpes), which could easily be due to chanceo In studies of this type, it is possible to obtain different results if the variables are absolute abundance of fruit (e.g., number of ripe fruits in an area) or richness or abundance of specific plant species eaten by each bird species assessed, instead of richness of fruiting ornithochorous plant species by vegetation type.